2003
DOI: 10.1677/joe.0.1780101
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNF-alpha production by pentoxifylline does not prevent endotoxin-induced decrease in serum IGF-I

Abstract: Sepsis and endotoxin (LPS or lipopolysaccharide) injection induce a state of growth hormone (GH) resistance leading to decreased circulating insulin-like growth factor (IGF)-I. Because the proinflammatory cytokines tumor necrosis factor (TNF)-and interleukin (IL)-1 inhibit the GHstimulated IGF-I expression in vitro, it was tempting to speculate that these two cytokines might play an important role in the reduction of circulating IGF-I levels caused by LPS. Pentoxifylline, a methylxanthine usually used in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
6

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
2
18
0
6
Order By: Relevance
“…In the present study, however, treatment of AH-130 bearers with PTX did not increase muscle IGF-1 mRNA, suggesting that TNF-␣ is not involved in the downregulation of IGF-1 expression, at least not in this model system. This observation is consistent with a previous report by Colson et al (16) showing that inhibition of TNF-␣ synthesis by PTX did not restore normal serum levels of IGF-1 in endotoxin-treated rats. By contrast, TNF-␣ has been shown to inhibit IGF-1 mRNA expression in C 2 C 12 myocyte cultures as well as in rat gastrocnemius (28,31,33).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, however, treatment of AH-130 bearers with PTX did not increase muscle IGF-1 mRNA, suggesting that TNF-␣ is not involved in the downregulation of IGF-1 expression, at least not in this model system. This observation is consistent with a previous report by Colson et al (16) showing that inhibition of TNF-␣ synthesis by PTX did not restore normal serum levels of IGF-1 in endotoxin-treated rats. By contrast, TNF-␣ has been shown to inhibit IGF-1 mRNA expression in C 2 C 12 myocyte cultures as well as in rat gastrocnemius (28,31,33).…”
Section: Discussionsupporting
confidence: 93%
“…2c and d; two-way ANOVA, p<0.001 or less for the glucose effect, p>0.2 for the time effect). Contrasting with the absence of a glucose effect, a 30-min exposure to IL-1β in the presence of G10 strongly and consistently activated NFκB DNA binding activity in these islets (p<0.01 or less The standard curve cDNA was either prepared from control precultured islets eventually treated for 6 h with 50 IU/ml IL-1β, or prepared from the liver of a rat infected with lipopolysaccharide (LPS-rat) [58] at each time point, n=3). Similar results were obtained using RPMI medium containing 10% heat-inactivated calf serum instead of BSA for preculture and culture of the islets (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…In hepatocyte cultures it has been reported that Tnfa was not able to alter basal Igf1 mRNA, but TNF-a inhibits the induction of Igf1 mRNA by GH (Ahmed et al 2006). Inhibition of Tnfa release by pentoxifylline administration prevents LPS-induced IL-1, whereas it is not able to prevent the increased release of PTGES2 (Shemi et al 2001), or the decrease in serum IGF1 and liver Igf1 mRNA (Colson et al 2003). These data support the hypothesis that Tnfa does not seem to be implicated in the LPS-induced decrease in basal Igf1 gene expression in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour necrosis factor-a (Tnfa) has been reported to inhibit Igf1 mRNA induction after GH stimulation both in vivo (Yumet et al 2002) and in vitro (Ahmed et al 2006). However, it has been demonstrated that suppression of Tnfa by pentoxiphylline fails to restore both circulating Igf1 levels and GH sensitivity in rats injected with LPS (Colson et al 2003).…”
Section: Introductionmentioning
confidence: 99%